A scandalous adventure - Marek, Lillian (Victorian adventures, 2016)
When Count Maximillian von Staufer's fiancée disappears, he discovers her doppelgänger, an Englishwoman, and persuades her to impersonate the missing lady. Little do the Englishwoman and her companion friend Olivia know that they will be pulled into a mystery of international intrigue and... romance.